A new genus of the tribe Parahiraciini (Hemiptera: Fulgoromorpha: Issidae) from Hainan Island - Meng, Rui; Qin, Daozheng; Wang, Yinglun (Zootaxa, 2015)
A new issid genus in the tribe Parahiraciini (Hemiptera: Fulgoromorpha: Issidae) is erected for Fortunia jianfenglingensis Chen, Zhang et Chang, 2014 (China: Hainan). Male of the species is described and illustrated for the first time. A key for the 15 genera of Parahiraciini is provided. Morphological peculiarity and phylogenetic position of the new genus and the distribution of the tribe Parahiraciini are briefly discussed.